Evaluation of Pain Perception During Orthodontic Debonding of Metallic Brackets with Simultaneous Application of TENS Therapy - Akash Rastogi; Payal Sharma; C. S. Ram; Shubhangi Jain; Monis Raza; Karan Tangri (Galenos Yayinevi, 2024)
Objective: The objective of the present study was to evaluate the effectiveness of transcutaneous electrical nerve stimulation (TENS) therapy on pain during the debonding procedure. Methods: A placebo-controlled, randomized split - mouth study was conducted on 30 orthodontic patients. The right and left anterior teeth in the maxilla and mandible were randomly allocated to the control and experimental groups (EG) and were stimulated. TENS application was made through a modified electrode probe that was used from an ammeter. The control group (CG) received the mechanical application of the device with no current, whereas the EG received progressively increasing current from 0.1 mA to the point where the patient experienced a mild tingling sensation for 60 s for each tooth. This was followed by a debonding procedure using an orthodontic debonding plier. Pain perception was recorded on a numerical rating scale after debonding each tooth. Results: The mean pain score was higher in the CG than in the EG, and the difference between the two groups was significant (p=0.001). The pain score was higher in the mandibular teeth than in the maxillary teeth, and the difference between the two groups was also significant (p=0.021). Pain score was higher in female subjects than in male subjects, and the difference between the two groups was significant (p=0.015). Conclusion: The application of TENS therapy results in pain reduction during the debonding procedure. The female subjects experienced more pain. Higher pain scores were recorded for the mandibular anterior teeth than for the maxillary teeth.